CONSUMER FINANCIAL SUSTAINABILITY: UNDERSTANDING VARIABILITY AND CHANGE IN ECONOMIC DYNAMICS - Fatmasari, Raden Roro; Padma Hanuun, Nazhira Nindya; Yolistina , Anggun (KRIEZ ACADEMY : Journal of development and community service, 2024)
The complex relationship between consumer financial sustainability, financial inclusion and sustainable economic development is an important focus in the context of addressing economic inequality and increasing access to financial services for vulnerable groups. Consumer financial sustainability plays a key role in ensuring the economic stability of individuals and households, while financial inclusion is a key means of ensuring that all people have equal access to necessary financial services. Sustainable economic development, on the other hand, requires active participation from all members of society to ensure equitable distribution of benefits. Through a comprehensive literature review, this article explores the relationship between consumer financial sustainability, financial inclusion, and sustainable economic development, as well as their impact on addressing economic inequality and increasing access to financial services for vulnerable groups. The analysis results show that increasing financial inclusion can reduce poverty and economic inequality, while consumer financial sustainability provides a strong foundation for sustainable economic growth. However, challenges in achieving greater financial inclusion and improving financial sustainability include a lack of financial literacy, limited access to financial services, and regulatory challenges. Therefore, policy suggestions include integrating financial education into formal education curricula, expanding access to financial services through financial technology innovation, and enhancing consumer protection through effective regulation. Thus, joint efforts from governments, financial institutions and civil society are needed to strengthen individual financial foundations and ensure broader financial inclusion, so as to support inclusive and sustainable economic growth.